MODEL INSTRUMEN TEST DIAGNOSTIK TWO TIERS CHOICE UNTUK ANALISIS MISKONSEPSI MATERI LARUTAN PENYANGGA - Antari, Winandari Dewi; Sumarni, Woro; Harjito, Harjito; Basuki, Joko (Universitas Negeri Semarang, 2020)
The research is a development research that aims to produce a product in the form of an instrument to detect chemical misconceptions in the buffer solution material. The research method used is the 4-D method, namely: Define, Design, Development, and Dissemination. The two tiers choice diagnostic test instrument product is in the form of 20 multiple choice questions. Data collection techniques were carried out with content validation sheets by material experts, difficulty level tests and teacher and student response questionnaires. The results of the content validity test by evaluation experts showed that diagnostic test questions were declared feasible to be used as an instrument for detecting high school students' misconceptions on the subject of buffer solution material with a total score of 105 and material experts with a total score of 145. questions, questions that are currently 6 items, and problems that are difficult there are 7 items. The results of the percentage of the average score obtained from the questionnaire seen from the aspect of practicality, readability and time in working on the problem resulted in 79.85%, 78.58% and 74.11% aspects. The conclusions of this study were two tiers choice diagnostic test instruments suitable for use as an instrument to detect high school students' misconceptions on the subject of buffer solution material.